1991
DOI: 10.1200/jco.1991.9.12.2148
|View full text |Cite
|
Sign up to set email alerts
|

A randomized comparison of single-agent doxorubicin and epirubicin as first-line cytotoxic therapy in advanced breast cancer.

Abstract: One hundred forty-one patients with advanced breast cancer who had not received prior chemotherapy were randomly assigned to receive doxorubicin 60 mg/m2 or epirubicin 90 mg/m2 every 3 weeks. These doses were selected to produce equivalent toxicities. All patients were assessed for toxicity, and 138 patients were assessable for response. After a median of five treatment cycles, 47% (32 of 68) of doxorubicin-treated patients achieved a partial or complete response. Response duration and survival were 10 and 12 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
44
0
2

Year Published

1998
1998
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(50 citation statements)
references
References 7 publications
1
44
0
2
Order By: Relevance
“…Doxorubicin treatment resulted in more bone marrow depression, mucositis and diarrhoea. In the study of Perez et al (1991), bone marrow toxicity of doxorubicin 60 mg m-2 and epirubicin 90 mg m-were almost superimposable, and the same results were found for gastrointestinal toxicity. Response percentages in this study were indentical, and the authors concluded that the higher dose of epirubicin had no advantages over the lower dose of doxorubicin.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…Doxorubicin treatment resulted in more bone marrow depression, mucositis and diarrhoea. In the study of Perez et al (1991), bone marrow toxicity of doxorubicin 60 mg m-2 and epirubicin 90 mg m-were almost superimposable, and the same results were found for gastrointestinal toxicity. Response percentages in this study were indentical, and the authors concluded that the higher dose of epirubicin had no advantages over the lower dose of doxorubicin.…”
Section: Discussionsupporting
confidence: 57%
“…Toxicity, however, was generally more pronounced in the doxorubicintreated patients. The four other studies compared the two drugs on an expected equimyelotoxic basis with doses of epirubicin ranging from 1.4 to 1.5 times the dose of doxorubicin (Jain et al, 1985;Taguchi et al, 1986;Hortobagyi et al, 1989;Perez et al, 1991). Similarly none of these studies showed significant differences in response rates, duration of response or survival between the two treatment arms.…”
Section: Discussionmentioning
confidence: 99%
“…Generally, because of cardiotoxicity, 900 mg/m 2 is recommended as the upper limit for the lifetime total dose of epirubicin [26][27][28], although there are reports of cardiac insufficiency occurring at 178 and 540 mg/m 2 [27,29]. The results of this study were also thought to have been influenced by the use of anthracyclines, which suggests the need for regular cardiac function tests, even when the total dose of anthracyclines is \900 mg/m 2 .…”
Section: Discussionmentioning
confidence: 66%
“…Response rates in anthracycline-naïve patients are reported to be in the 25%-50% range [58][59][60][61] . Prior anthracycline exposure, including evaluation of total cumulative dose and other cardiac risk factors (for example, coronary artery disease, prior myocardial infarction, prior mediastinal radiotherapy) necessitate a baseline review of cardiac ejection fraction and monitoring thereafter 62 .…”
Section: Anthracycline and Anthracenedionementioning
confidence: 99%